SEMIOTIKA TANDA INFOGRAFIS KOMISI PEMBERANTASAN KORUPSI (KPK): Semiotika Tanda Infografis Komisi Pemberantasan Korupsi (KPK) - Pungky Febi Arifianto (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2018)
In term of its presentation of data, qualitative descriptive research is implemented as the method. To interpret the handling of corruption conducted by Indonesia's Corruption Eradication Commission, Charles S. Pierces’ theory of signs classification in icon, index, and symbol is utilized as the approach. Disclosure of meaning the signs itself applies of Rolland Barthes’s connotation interpretations in significance. The Five Codes in significances are divided into Hermeneutic, Proairetic, Semantic, Symbolic, and Cultural. Visual infographic analysis in corruption’s handling by Indonesia's Corruption Eradication Commission is expected for being able to give a discourse in semiotic interpretation to signs and meaning in infographics. Theoretically, the purpose of this analysis will give depiction about a scientific approach to visual communication design theory in sending message through sign-system in each visual elements in infographics.